1998
DOI: 10.1016/s0039-128x(98)00042-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term treatment with aromatase inhibitor on testicular function of adult male bonnet monkeys (M. radiata)

Abstract: The role/need for estrogen in regulating testicular function of adult male bonnet monkeys (M. radiata) has been investigated by dosing orally a group of five normal males 2.5 mgs of CGP 47645, a long-acting nonsteroidal aromatase inhibitor (AI), once every 5 days for over 150 days. Such treatment resulted in a 10-fold increment in nocturnal serum testosterone (T) levels, which were sustained for 85 days of treatment, and a twofold increment in basal serum T levels was present throughout the 150 days of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
8

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 41 publications
3
31
0
8
Order By: Relevance
“…Nevertheless, several studies involving the inhibition of aromatisation have shown a consistent and rapid increase in testosterone concentrations (50%) in humans (Bhatnagar et al 1992, Trunet et al 1993, Hayes et al 1999, primates (Ellinwood et al 1984, Dukes et al 1996, Shetty et al 1998 and dogs (Juniewicz et al 1988). In the present study, an increase in plasma testosterone concentrations occurred within 1 week of anastrozole treatment and was maintained for approximately 5 months but not beyond this time.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, several studies involving the inhibition of aromatisation have shown a consistent and rapid increase in testosterone concentrations (50%) in humans (Bhatnagar et al 1992, Trunet et al 1993, Hayes et al 1999, primates (Ellinwood et al 1984, Dukes et al 1996, Shetty et al 1998 and dogs (Juniewicz et al 1988). In the present study, an increase in plasma testosterone concentrations occurred within 1 week of anastrozole treatment and was maintained for approximately 5 months but not beyond this time.…”
Section: Discussionsupporting
confidence: 70%
“…This is in contrast to treatment of dogs with fadrozole for 6 months, which had no effect on sperm counts or gross testicular morphology ( Juniewicz et al 1988). Long-term treatment of adult bonnet monkeys with an analogue of letrozole resulted in a 90% reduction in sperm production after treatment for 55 days; flow cytometric analysis demonstrated a reduction in round and elongating spermatids, implying a defect in spermiogenesis (Shetty et al 1998). Administration to adult male rats of a protein purified from the ovary that had aromatase inhibitory activity also induced a reduction in the number of elongate spermatids (Tsutsumi et al 1987), and a similar late-onset lesion in ArKO mice has recently been described .…”
Section: Discussionmentioning
confidence: 68%
“…In human adult seminiferous tubules cultured in vitro, 17b-estradiol (E) acts as a germ cell survival factor [Pentikainen et al 2000]. This observation is supported by a study in male monkeys treated with an aromatase inhibitor which displayed a decrease in germ cell number [Shetty et al 1998]. Very recently it was demonstrated that E stimulates DNA synthesis in rat spermatogonia, an effect also maintained by the dihydrotestosterone metabolite, 5a-androstane-3b,17b-diol via interaction with ERb [Wahlgren et al 2008].…”
Section: Discussionmentioning
confidence: 94%
“…Oestrogen production and androgen bioavailability are regulated by cytochrome P450 aromatase activity. Although the role of the P450 aromatase in human spermatogenesis is still under investigation, the noteworthy decrease in round and elongated spermatids after the administration of an aromatase inhibitor in rat 23 and monkey, 24 and the P450 aromatase localisation in the germinal epithelium of the adult mouse testis, primarily in the Golgi region of round spermatids, throughout the cytoplasm of elongating spermatids and along the flagella of late spermatids, 25 support the idea that P450 aromatase is important for spermatogenesis in humans'.…”
Section: Discussionmentioning
confidence: 99%